Homotopy Analysis Solution for Magnetohydrodynamic Squeezing Flow in Porous Medium. (22nd June 2016) - Ullah, Inayat; Rahim, M. T.; Khan, Hamid; Qayyum, Mubashir
Abstract : The aim of the present work is to analyze the magnetohydrodynamic (MHD) squeezing flow through porous medium using homotopy analysis method (HAM). Fourth-order boundary value problem is modeled through stream functionψ ( r, z ) and transformationψ ( r, z ) = r 2 f ( z ) . Absolute residuals are used to check the efficiency and consistency of HAM. Other analytical techniques are compared with the present work. It is shown that results of good agreement can be obtained by choosing a suitable value of convergence control parameterh in the valid regionR h . The influence of different parameters on the flow is argued theoretically as well as graphically.